Isoniazid alone in the treatment of tuberculosis - Two years experience in previously untreated patients - Vargas Jiménez, Federico (1957)
Forty-three cases of advanced pulmonary tuberculosis were treated for the first time for at least nine months of isoniazid to daily doses of 5 and 10 mg. per kl. In 36 cases the administration of isoniazid was extended to twelve months, and at 29, 15 and 21 months. In 34 cases kept under observation for two years, 83% were no longer infectious and 71% all cavities were closed. The analysis of these results provides clinical evidence to suggest that the therapeutic efficacy of the regimen with the drug isoniazid alone is not dissimilar to the therapeutic efficacy of isoniazid is streptomycin or isoniazid, PAS, and that should be investigated higher doses of isoniazid.